Efficacy of fungicides with different modes of action in raspberry spur blight (Didymella applanata) control - Stević, Milan; Pavlović, Biljana; Tanović, Brankica (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
Efficacy trials of four multi-site fungicides (copper hydroxide, mancozeb, chlorothaloniland dithianon), as well as six fungicides with specific modes of action (fluopyram, boscalid, fluazinam, tebuconazole, azoxystrobin and pyraclostrobin) in raspberry spur blight (Didymella applanata) control were carried out in the seasons 2014 and 2016. The experiments were conducted as a randomized block design with four replicates in a commercial raspberry orchard in the locality Trešnjevica (Arilje) in western Serbia. All fungicides were applied preventively, four times until the beginning of harvest and once after harvest. The effects of the products tested were assessed three weeks after the last fungicide application according to the intensity of cane infection. Disease severity in control (untreated) plots were 53.7 (2014) and 76.3% (2016). In both years, the highest efficacy was achieved by tebuconazole (96.3 and 99.6%), followed by fluopyram (95.7 and 99.3%) and boscalid (94.7 and 95.9%). The broad-spectrum multi-site fungicides mancozeb, chlorothalonil, copper hydroxide and dithianon were effective against D. applanata and they reduced disease severity significantly, in comparison with the untreated plots. The efficacy of these compounds was between 64.4 and 81.7%. Conversely, azoxystrobin, pyraclostrobin, and fluazinam showed very low efficacy(13.7-37.8%) in control of raspberry spur blight.
Keywords: Didymella applanata; Fungicides; Chemical control; Raspberries